Influence of depression and self-esteem on oral health-related quality of life in students - Oancea, Roxana (J Int Med Res, 2020)
OBJECTIVE: We aimed to investigate the influence of depression and self-esteem on oral health-related quality of life (OHRQoL) in students. METHODS: Among the 67 included participants, we measured self-esteem using the Rosenberg Self-Esteem Scale, severity of depression using the Patient Health Questionnaire-9 (PHQ-9), personality dimensions with the Neuroticism–Extraversion–Openness Five-Factor Inventory, and OHRQoL using the Oral Health Impact Profile 49 (OHIP-49). RESULTS: Among all participants, 7.5% (n = 5) had the dominant personality trait openness to experience, 11.9% (n = 8) presented a neurotic personality type, and 64.% (n = 11) had an extraverted personality type. The most frequent was conscientious personality type, accounting for 64.2% (n = 43) of participants. Our results showed a significant correlation between increased PHQ-9 scores and OHIP scores (Spearman’s r = 0.280); thus, participants with poorer oral health tended to have more severe depression. An increase in depression severity was significantly and positively correlated with increased scores across the other two OHIP subcategories, physical pain (Spearman’s r = 0.314) and physical disability (Spearman’s r = 0.290). CONCLUSION: The presence and severity of depression influences OHRQoL. An important factor in the presence of depression and level of self-esteem is the personality type, especially the neuroticism dimension.